Dampness and mold at home and at work and onset of insomnia symptoms, snoring and excessive daytime sleepiness. (June 2020) - Wang, Juan; Janson, Christer; Lindberg, Eva; Holm, Mathias; Gislason, Thorarinn; Benediktsdóttir, Bryndís; Johannessen, Ane; Schlünssen, Vivi; Jogi, Rain; Franklin, Karl A.; Norbäck, Dan
Highlights: Dampness/mould at home can be risk factors for adult onset of sleep disturbances. Dampness/mould at work can increase adult onset of sleep disturbances. Combined dampness at home and at work can further increase the onset. Abstract: Aim: To investigate whether exposure to dampness and mold at home and at work induce sleep disturbances and daytime sleepiness among adults. Materials and methods: Associations between onset of sleep disturbances and dampness, mold and mold odor at home and at work were investigated in a cohort of 11, 318 adults from the population in Iceland, Norway, Sweden, Denmark and Estonia. The participants answered a questionnaire at baseline and 10 years later, with questions on sleep disturbances, including difficulty initiating sleep (DIS), difficulty maintaining sleep (DMS), early morning awakening (EMA), insomnia symptoms, snoring and excessive daytime sleepiness (EDS). Multiple logistic regression models were applied to estimate associations adjusting for potential confounders including gender, age, smoking habit at baseline, change of smoking habit from baseline to follow up, BMI at baseline, change of BMI from baseline to follow up, education level at follow up, allergic rhinitis at baseline, doctor diagnosed asthma at baseline and chronic bronchitis at baseline. Results: Baseline floor dampness, visible mold and mold odor at home increased onset of DIS, DMS, EMA, insomnia symptoms and snoring during follow up (OR 1.29–1.87). Any sign of dampness at baseline increased onset of DIS (OR 1.28, 95%CI 1.06–1.55), DMS (OR 1.17, 95%CI 1.02–1.34) and insomnia symptoms (OR 1.18, 95%CI 1.03–1.36). Dampness at home during follow up increased onset of DIS, DMS, EMA, insomnia symptoms and EDS (OR 1.17–1.36). Dampness at work during follow up increased onset of DIS, EMA, insomnia symptoms and EDS (OR 1.16–1.34). Combined dampness at home and at work during follow up increased the risk of onset of DIS, DMS, EMA, insomnia symptoms and EDS (OR 1.29–1.74). Conclusions: Dampness and mold at home and at work can increase the development of insomnia symptoms, snoring and EDS among adults.